2009
DOI: 10.1080/00365510802430964
|View full text |Cite
|
Sign up to set email alerts
|

Association of C34TAMPD1gene polymorphism with features of metabolic syndrome in patients with coronary artery disease or heart failure

Abstract: C34T AMPD1 polymorphism may be associated with reduced frequency of obesity in CAD patients and of hyperglycaemia and diabetes in both CAD and HF patients. Morphometric parameters associated with adipose tissue distribution and parameters of glucose metabolism should be analysed as potential confounders in further studies on the role of polymorphisms of AMPD1 and other genes associated with AMP and adenosine metabolism in cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
1
23
2
Order By: Relevance
“…SBP was significantly lower in the CC carriers, in contrast to the results reported by Safranow et al (2009). In comparison with Safranow et al's study (2009) we detected 30 EH subjects who were carriers of the TT genotype.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…SBP was significantly lower in the CC carriers, in contrast to the results reported by Safranow et al (2009). In comparison with Safranow et al's study (2009) we detected 30 EH subjects who were carriers of the TT genotype.…”
Section: Discussioncontrasting
confidence: 82%
“…The same outcomes were reported by Safranow et al (2009) using the same method (RFLP), with clear evidence from genotyping. Our results revealed that in the Malaysian population, the most common AMPD1 polymorphism (C34T) is strongly associated with EH (P ˂ 0.001).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Other obesity-related genes including ADIPOQ, leptin receptor, and fat mass obesity-related genes have also been described with respect to manifestation of metabolic syndrome and CAD/MI 90 . While genes, such as the PPARs 91 have been discussed as independent risk for CAD 88 , several of them may share common variants for metabolic syndrome with CAD/MI, among themselves and/or with others, including Ang II 92 , AMP deaminase-1 93 and ACE 91 genes. For example, the risk of acquiring CAD in patients with T2DM appears to increase significantly in the presence of the several gene variants such as those of the transcription factor 7-like 2 (TCF7L2) 94 and E-selectin genes 95 .…”
Section: In F a C T D I A B E T I C P A T I E N T S A R E T H O U Gmentioning
confidence: 99%